Knowledge, perception and willingness of mothers to accept malaria vaccine for their children in Ondo West Local Government, Ondo State - Oluwafisayo Deborah Andrew (Discover Public Health)
Abstract Background Significant stride has been made to control malaria in the past. Recently malaria vaccine was developed as a control measure for malaria. However, previous vaccination programmes in Nigeria has faced issue with high rate of hesitancy. This study therefore assessed the knowledge, perception and willingness of mothers to accept malaria vaccines for their children prior to its availability for use. Methods A mixed-method approach comprising both quantitative survey and qualitative interview was conducted among consenting mothers. For the quantitative part of the study, a multi-stage cluster sampling technique was used to recruit participants (n = 359) from five enumeration areas in Ondo west Local Government, Nigeria. Data was collected through an in-depth interviews (IDIs) using pre-tested and structured questionnaires. Data were analyzed using descriptive statistics like frequency and percentages for data summarization. Bivariate and multivariate logistic regression analysis was performed and strength of association was assessed by odds ratio at 95% confidence intervals. For the qualitative aspect, 15 mothers were selected randomly for the in-depth-interview, leveraging the interviewer guide for data collection and thematic content analysis was performed. Results The mean age of the respondents was 31.3 ± 6.8 years. 223 (62.1%), demonstrated good knowledge about the malaria vaccine. In terms of perception towards malaria vaccine, 88 (55.7%), exhibited a positive attitude, while 70 (44.3%), displayed a poor attitude. 337 (93.9%) of mothers expressed their willingness to vaccinate their children against malaria one hundred. Sixty-four (45.7%) mothers expressed worry about potential adverse reactions their child might experience from the vaccine, 140 (39%) of the mothers believed that their husband or partner's refusal to vaccinate their children could impact their decision to accept the malaria vaccine. The predictors to willingness to accept malaria vaccine were good knowledge (AOR: 2.5, 95% CI: 1.04–6.05, p = 0.020), and good perception (AOR: 8.7, 95% CI: 2.53–29.96, p = 0.001). Based on the qualitative findings, the most common reasons for vaccine refusal among the population were concern about safety, potential side effects and spousal influence. Conclusion The study revealed a generally positive knowledge and perception towards the malaria vaccine. While there is high acceptance of vaccine among mothers, barriers including safety, potential side effects, and influence from family dynamics, particularly spousal refusal, might hinder this acceptance. Targeted educational interventions and community engagement strategies is needed to address misconceptions and build trust.